Are societies becoming more self-centric? Evidence from five decades of popular music spanning three continents - Marius Golubickis; Parnian Jalalian; Leoni S. Masroujah; Esther S. Selvaraj; Yadvi Sharma; Siew Hwee Seow; Adriana Borrego-Guerrero; Sadie Marr; C. Neil Macrae (PLoS ONE, 2026)
A commonly expressed claim is that societal self-centrism has increased over recent decades. To examine this assertion, we analyzed an influential cultural product — popular music — to track changes in self-focus across five decades and three continents. Using an established linguistic analysis technique, personal pronoun usage (i.e., a marker of self-focus) was quantified in the ten most popular songs each year from 1970 to 2019 in the United States, Germany, Japan, and Hong Kong. Results indicated a significant increase in self-focused language over time in individualistic societies (i.e., United States & Germany), whereas no comparable trend was observed in more collectivistic contexts (i.e., Japan & Hong Kong). These findings demonstrate how public artifacts can be leveraged to investigate cultural variation in the expression of self-centrism.